Clustering Based Energy Efficient Protocols For Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2014)
Sensor networks have become an emerging new tool for habitat monitoring in nature preserves, it monitors and gathering events in hazardous environments, it does the work of buildings surveillance, monitoring the enemy activities in a battlefield environment. Sensor nodes have limited energy resources, less storage capacity and they are energy constrain. Efficient routing protocols are very critical to design in order to prolong the lifetime of the sensor nodes. Sensor networks are mainly designed for monitoring and reporting events though sensor nodes are application dependent, designing a single routing protocol cannot be efficient for sensor networks for all applications. In this paper, we first analyze the requirements, similarities and distinguish between sensors networks and MANETs (Mobile Ad hoc Networks). Cluster formation reduces the nodes involved in transmission & conserves the energy. The cluster based protocols are energy efficient & prolong the network lifetime when compared to other protocols.